Quality and Quantity of Dairy Cow Milk Production in View of Differences in Concentrate Use at KUD Kertajaya Kandangan, Kediri Regency, East Java - Oriza Cahya Rahmadiati; Siti Eliana Rochmi; M. Gandul Atik Yuliani; Anwar Ma'ruf; Miyayu Soneta Sofyan; Agung Budianto Achmad; Dony Chrismanto (Universitas Airlangga, 2023)
Background: Differences in the use of concentrates in dairy cows cause differences in the quantity and quality of milk produced. Purpose: To compare the quality and quantity of milk between dairy cows fed concentrate A and concentrate B. Methods: This observation was carried out at KUD Kertajaya Kandangan Kediri using 40 cows with a ratio of 20 dairy cows fed concentrate A and 20 cows dairy cows fed concentrate B. The quality of cow's milk samples was tested using a lactoscan machine, and then the quantity was measured at the time of milking using a scaled milk can. Results: The results showed that the quality of dairy cows fed with concentrate A had an average pH of 6.495±0.176, milk specific gravity of 1,0241±0.0004 g/ml, a fat content of 5,241±2.614%, protein of 3,335±0.294%, non-solid fat of 8.542±0.518% and total solid of 13.707±2.612% with an average milk yield of 15.7±2.273 liters per day while the quality of dairy cows fed with concentrate B had an average pH of 6.425±0.102, milk Specific Gravity of 1,0244±0.0005 g/ml, Fat Content of 6,447±2.621%, Protein of 3.284±0.213%, non-solid fat of 9.134±0.6313% and total solid of 15.459±2.752%% with the average milk produced is 15.5±2.140 liters per day. Conclusion: The quality and quantity of milk of dairy cows fed concentrates A and B have a noticeable difference (P<0.05) in terms of solid nonfat (SNF) and total solids. Concentrate B has a higher percentage of solid nonfat and total solid than concentrate A.